Ageing, learning and health: making connections. Issue 5 (2nd September 2016) - Mestheneos, Elizabeth; Withnall, Alexandra
Abstract: The health of ageing populations is a real concern across the world so that the concept of active ageing has been advocated as a framework for appropriate educational policies and programmes to support people as they grow older. The other elements discussed here are health and healthy life expectancy (HLE) acknowledging that as people age, they may suffer from a range of chronic illnesses. How strong is the evidence that improving access to, and involvement in later life learning is an effective strategy for improving health and can it help with health problems? Reviewing some of the available evidence, we found that studies are frequently not comparable, that they frequently confuse concepts of health and well-being and do not always demonstrate causal effects. We also question whether later life learning can be successful in reducing lifelong socio-economic inequalities although some targeted interventions are beginning to appear in different countries. We conclude that it is important to rethink attitudes to active ageing if current gains in healthy LE are to continue.